Method for manufacturing metal or alloy thin film imparted anion exchange membrane

By applying silver catalyst nuclei and using an electroless plating bath with specific reducing agents, the method overcomes the limitations of existing technologies in forming metal or alloy thin films on anion exchange membranes, achieving versatility and cost-effectiveness.

JP2025039048APending Publication Date: 2025-03-21WASEDA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023145798
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing methods for forming metal or alloy thin films on anion exchange membranes are limited by the use of expensive palladium as a catalyst and the inability to electrolessly deposit a wide range of metal species.

Method used

A method involving the application of silver catalyst nuclei to anion exchange membranes, followed by immersion in an electroless plating bath containing metal salts, amine borane, and a specific reducing agent, allowing for the deposition of various metal or alloy thin films.

Benefits of technology

This method enables the electroless analysis of a wide range of metal species on anion exchange membranes using a less expensive and more versatile catalyst nucleus than palladium, resulting in the formation of durable and efficient metal or alloy thin films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039048000002
    Figure 2025039048000002
  • Figure 2025039048000003
    Figure 2025039048000003
  • Figure 2025039048000001
    Figure 2025039048000001
Patent Text Reader

Abstract

To provide a method for manufacturing a metal or alloy thin film imparted anion exchange membrane that uses a catalyst nucleus having a high-mounting possibility and inexpensive as compared to palladium but allows electroless deposition of a wide range of metal species on an anion exchange membrane.SOLUTION: A method for manufacturing a metal or alloy thin film imparted anion exchange membrane including a metal or alloy thin film on at least one of surfaces of an anion exchange membrane includes the steps of: imparting a silver catalytic nucleus to at least one of the surfaces of the anion exchange membrane; and immersing the anion exchange membrane imparted with the silver catalytic nucleus into an electroless deposition bath including (a) one or more types of metallic salts, (b1) amine borane, and (b2) a reductant in accordance with the metal or alloy to be deposited to reduce the metal salts and deposit the metal or alloy at the surface imparted with the silver catalytic nucleus of the anion exchange membrane.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an anion exchange membrane provided with a thin metal or alloy film. [Background technology]

[0002] Electroless plating is a conventional technique for applying functional thin films to non-conductive substrates. Because electroless plating does not use external power, pretreatment is required to apply catalytic nuclei to the substrate, which initiate the reaction of a reducing agent as an electron source. These catalytic nuclei promote the reduction of metal cations in the electroless plating bath, forming a thin metal film on the surface of non-conductive substrates such as glass, ceramics, and plastics using the cations as precursors.

[0003] In recent years, anion exchange membranes have been attracting attention as an important element of electrochemical energy devices, and a major example of the application of anion exchange membranes is water electrolysis equipment. As the demand for green hydrogen is on the rise, there is a demand for such equipment to have higher performance and lower cost. Water electrolysis equipment that uses anion exchange membranes as the electrolyte membrane has a wide range of materials that can be used for the cell components, and has the potential to achieve high electrolysis performance while achieving low cost. For example, anion exchange membranes in water electrolysis equipment are used to separate OH - Because it functions as a pathway and enables the water electrolysis process in an alkaline environment, it does not require the use of acid-resistant precious metals, making alkaline water electrolysis cost-effective.

[0004] The technology of directly forming a thin metal film on a polymer membrane such as an ion exchange membrane can be used for many applications. For example, the technology of directly forming an electrode catalyst material for electrolysis reaction on an anion exchange membrane is one of the effective methods of implementing an anion exchange membrane in a water electrolysis device. This method of directly adding a catalyst reduces the resistance between the electrode catalyst and the anion exchange membrane, and therefore exhibits good electrolysis performance. In the conventional method, an ionomer was used to bond the electrode to the anion exchange membrane, but if an electrode catalyst can be formed on the membrane without using an ionomer, which is likely to deteriorate due to heat, it will lead to the creation of highly durable electrode components and the development of devices that realize more stable operation. The electroless plating method is expected to be a technology for directly forming an electrode catalyst on an anion exchange membrane without using an ionomer.

[0005] The surface of anion exchange membranes consists of a hydrocarbon-based backbone and side chains with cationic terminals, such as quaternary ammonium functional groups. Such positively charged functional groups generally have difficulty interacting with metal cations, which also have a positive charge, making it difficult to form catalyst particles using such metal cations as precursors. In a conventional approach, the surface of a non-conductive substrate is provided with functional terminals with unshared electron pairs that can coordinate to such metal cations, thereby increasing the interaction between the metal cations and the surface, thereby forming catalyst particles. However, this is difficult to do when using anion exchange membranes as a substrate. Therefore, a different approach is required to apply a catalyst to anion exchange membranes.

[0006] The present inventors proposed a new electroless plating process on an anion exchange membrane (Non-Patent Document 1). They found that the anions in the bath play an important role in modifying the catalyst particles, using palladium. Among the anions, Cl was especially important. - Pd is the precursor of palladium catalyst particles. 2+It was found that the anion exchange membrane surface is provided with a sufficiently strong bond between the palladium and the positively charged functional groups. Based on this, a pretreatment process was developed in which the anion exchange membrane is immersed in a PdCl2 / HCl solution, which allows palladium catalyst particles to be satisfactorily deposited, and an electroless plating reaction is then carried out on the palladium catalyst particles to form a metal or alloy thin film on the anion exchange membrane. On the other hand, for example, when a conventionally known sensitization process using a tin-containing solution is applied before the pretreatment process of immersion in a PdCl2 / HCl solution, Pd 2+ The adsorption of the metal is hindered and the subsequent deposition reaction is also inhibited, making electroless plating difficult, and the incompatibility of such conventional processes has also been confirmed. [Prior art documents] [Non-patent literature]

[0007] [Non-Patent Document 1] Electrochemistry,89(2),192-196(2021) Summary of the Invention [Problem to be solved by the invention]

[0008] The electroless plating process proposed in Non-Patent Document 1 offers the possibility of producing a metal or alloy thin film directly on the surface of an anion exchange membrane. However, since expensive palladium is used as the catalytic core metal species for the plating reaction, there is a problem that it is not versatile. On the other hand, with catalytic core metal species other than palladium, the metals that can be electrolessly deposited are sometimes limited, so there is also a problem with versatility.

[0009] The present invention has been made in consideration of the above-mentioned circumstances, and has an objective of providing a method for manufacturing an anion exchange membrane with a metal or alloy thin film, which enables electroless deposition of a wide range of metal species onto the anion exchange membrane while using a catalyst nucleus that is highly implementable and less expensive than palladium. [Means for solving the problem]

[0010] In order to solve the above problems, the present inventors have conducted intensive research and found a process that solves the problem of versatility by improving both the pretreatment and the electroless plating process as the catalyst nucleus formation process. In the catalyst nucleus formation process, relatively inexpensive silver was examined as an alternative to palladium in Non-Patent Document 1, and it was found that silver catalyst nucleus particles were formed on the anion exchange membrane. However, Non-Patent Document 1 discusses the mechanism by which electroless plating on anion exchange membranes is possible by using palladium catalyst nuclei, but it is difficult to apply this knowledge directly to electroless plating using other metal species catalyst nuclei. For example, with silver catalyst nuclei, metal or alloy thin films are not deposited even when conventional reducing agents are used alone, and Ni-P alloys are not deposited even when hypophosphite is used. However, it was found that various metal or alloy thin films can be deposited on anion exchange membranes by using a specific reducing agent, amine borane, as an essential reducing agent and combining it with other reducing agents, and this invention was completed. That is, the method for producing a metal or alloy thin film-applied anion exchange membrane of the present invention is a method for producing a metal or alloy thin film-applied anion exchange membrane having a metal or alloy thin film on at least one surface of the anion exchange membrane, comprising the steps of: providing silver catalyst nuclei on at least one surface of the anion exchange membrane; and The method is characterized by including a step of immersing an anion exchange membrane having silver catalytic nuclei imparted thereto in an electroless deposition bath containing (a) one or more metal salts, (b1) an amine borane, and (b2) a reducing agent appropriate for the metal or alloy to be deposited, thereby reducing the metal salt and precipitating the metal or alloy on the surface of the anion exchange membrane having the silver catalytic nuclei imparted thereto. Effect of the Invention

[0011] According to the present invention, electroless deposition of a wide range of metal species onto an anion exchange membrane is possible using a catalyst nucleus that is less expensive than palladium. [Brief description of the drawings]

[0012] [Figure 1](A) is a photograph of an anion exchange membrane after immersion in a bath prepared by mixing dimethylamine borane (DMAB) and hypophosphite with an aqueous solution containing nickel salts and iron salts (precipitate layer visible), and (B) is a photograph of an anion exchange membrane after immersion in a bath containing only hypophosphite (precipitate layer not visible). [Diagram 2] The catalytic performance evaluation is shown when the precipitated NiFeP layer is used as a catalyst for hydrogen generation reaction by using the NiFeP-imparted anion exchange membrane prepared in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the embodiment of the present invention will be specifically described. The method of the present invention is a method for producing an anion exchange membrane having a metal or alloy thin film on at least one surface of the anion exchange membrane, and includes the following steps (A) and (B): (A) providing silver catalyst nuclei on at least one surface of the anion exchange membrane; (B) A process of immersing the anion exchange membrane having the silver catalytic nuclei imparted thereto in an electroless deposition bath containing (a) one or more metal salts, (b1) an amine borane, and (b2) a reducing agent appropriate for the metal or alloy to be deposited, thereby reducing the metal salt and precipitating the metal or alloy on the surface of the anion exchange membrane having the silver catalytic nuclei imparted thereto.

[0014] In the initial stage of deposition in step (B), the reaction of amine borane is activated by the silver catalyst nucleus, and the metal salt (a) is reduced to deposit a metal or alloy. The deposited metal or alloy then activates the reaction of the reducing agent (b2), promoting electroless deposition and resulting in the deposition of a metal or alloy thin film.

[0015] It is difficult to form a metal other than palladium as a catalytic nucleus on an anion exchange membrane that has a positive charge on the surface and does not have an unshared electron pair by only using the knowledge of Non-Patent Document 1. For example, even if nickel is used instead of palladium, it cannot be provided as a catalytic nucleus. In other words, the chloride ion, which is considered to be a factor in the formation of catalytic nuclei on an anion exchange membrane in Non-Patent Document 1, is replaced by [NiCl4] 2- When silver is coordinated in the form of a precursor, no nickel catalytic nucleus is formed. When silver is used as the catalytic nucleus, the reducing agent that can be used is limited. For example, when a deposition bath is used in which the reducing agent (b1) amine borane is not used and only hypophosphite (b2) is added, no metal or alloy thin film is formed. In the present invention, the reaction of the amine borane is activated by the silver catalytic nucleus, and the metal salt (a) is reduced to deposit a metal or alloy, and then the reaction of the reducing agent (b2) is activated by the deposited metal or alloy, promoting electroless deposition, and a metal or alloy thin film is deposited. This allows various metal or alloy thin films to be formed on the anion exchange membrane.

[0016] The anion exchange membrane is not particularly limited as long as it has a selective permeability function that prevents the passage of cations and allows only anions to pass, has water absorption ability, is capable of electrophoresis by direct current electric energy, and is capable of ion regulation of the solution present between the electrodes. For example, a membrane of an anion conductive polymer composed of a hydrocarbon-based main chain and a side chain containing a positively charged quaternary ammonium functional group can be mentioned. An example of a side chain containing a quaternary ammonium functional group is one derived from a trimethylbenzylammonium compound.

[0017] In step (A), silver catalytic nuclei for electroless deposition (for the oxidation reaction of the reducing agent) are formed on the surface of the anion exchange membrane. In step (B), electrons produced in the oxidation reaction of the reducing agent are received by metal ions in the bath, causing reduction, which results in the deposition and accumulation of a metal or alloy. Since the reaction of the reducing agent is the driving force here, controlling this reaction leads to controlling the entire deposition reaction. Step (A) also serves as a catalysis step for modifying the surface of the anion exchange membrane with catalytic nuclei for the reducing agent, with the intention of preventing oxidation-reduction from occurring in the bath in step (B).

[0018] In order to form stable and dense catalytic nuclei, it is important to have stable adsorption of the catalytic nuclei precursor. For example, palladium is - It has been reported that a stable catalyst nucleus precursor can be formed on the surface of an anion exchange membrane by combining it with a specific anion species such as palladium (Non-Patent Document 1), but palladium is expensive and has low practicality, making the process less versatile. If another metal species is selected as the catalyst nucleus, the deposited metal species is limited. In the present invention, silver, which is more practical, is provided as the catalyst nucleus, and amine borane (b1) and another reducing agent (b2) are used in combination as the reducing agent, thereby providing a highly versatile process that does not limit the deposited metal species.

[0019] The bath for modifying the silver catalyst nucleus precursor contains silver salt and chloride ions (Cl - ) is added. Examples of silver salts include AgNO3. Cl - Examples of sources of silver salts and Cl include HCl. - The addition of Cl forms a silver chloride complex, which makes it easier for the precursor to adsorb on the surface of the anion exchange membrane. Adjusting the anion species that bridges the interaction between the catalyst precursor and the functional groups on the surface of the anion exchange membrane is one of the key factors for achieving electroless deposition on the anion exchange membrane. - is the precursor Ag + It is presumed that the Ag catalyst provides a sufficiently strong bond between the Ag and the positive functional groups of the anion exchange membrane, which allows the precursor to be strongly adsorbed on the membrane surface and thus allows the silver catalyst particles to be well deposited. +Since cations alone do not strongly interact with the positively charged functional groups on the anion exchange membrane surface that do not have an unshared electron pair, such as trimethylammonium, the catalyst precursor on the anion exchange membrane surface, Cl - It is believed that a sufficiently strong interaction between the silver complex containing Cl and the functional groups on the anion exchange membrane surface is important. - Ag + It is believed to play an important role in stabilizing the cation adsorption structure.

[0020] The content of the silver salt in the bath for modifying the silver catalytic nucleus precursor is not particularly limited, but considering both the high density and uniform adsorption of the silver catalytic nucleus precursor and the fact that the silver salt is difficult to dissolve, it is preferably about 0.01M. + The condition for stable ion existence is preferably acidic, but since hydrochloric acid is added as a source of chloride ions, the liquid tends to be acidic unless special procedures are performed. In addition to silver salt and chloride ions, other components may be added to the bath. The other components are not particularly limited, but examples thereof include those described below as other components that can be added to the electroless deposition bath in step (B).

[0021] The temperature of the bath for immersing the anion exchange membrane in the bath to modify the silver catalyst nucleus precursor is not particularly limited, but can be performed at room temperature. The immersion time is not particularly limited, but is preferably 30 to 90 seconds, more preferably about 60 seconds. The anion exchange membrane may be subjected to a pretreatment such as acid washing or water washing to clean the surface before immersion.

[0022] After the surface of the anion exchange membrane is modified with the silver catalyst nucleus precursor, the anion exchange membrane is immersed in a deposition bath containing a reducing agent to reduce and deposit the silver catalyst nucleus. Examples of the reducing agent include amine borane. The content of the reducing agent in the deposition bath is not particularly limited, but is preferably 0.01 to 0.1 M, more preferably about 0.05 M, in terms of deposition rate, uniform deposition, and the like. The pH of the deposition bath is not particularly limited. In addition to the reducing agent, other components may be added to the deposition bath. Examples of the other components include, but are not particularly limited to, those described below as other components that can be added to the electroless deposition bath in step (B).

[0023] The temperature of the bath for immersing the anion exchange membrane in the precipitation bath to precipitate the silver catalyst nuclei is not particularly limited, but can be room temperature. The immersion time is not particularly limited, but is preferably 30 to 90 seconds, more preferably about 60 seconds. The anion exchange membrane may be subjected to a pretreatment such as washing with water to clean the surface before immersion.

[0024] In step (B), the anion exchange membrane to which the silver catalyst nuclei have been applied is immersed in an electroless deposition bath, and the metal salt (a) is reduced to deposit a metal or alloy on the surface to which the silver catalyst nuclei have been applied. The metal salt (a) is not particularly limited as long as it is soluble in the electroless deposition bath depending on the target metal or alloy thin film. For example, a salt containing a transition metal element can be used. Examples of the transition metal element include nickel, iron, cobalt, copper, platinum, palladium, gold, molybdenum, tungsten, rhenium, etc. The metal salt (a) may be any of various inorganic salts that are soluble in the electroless deposition bath, particularly water-soluble. Examples of the inorganic salt include halides such as sulfates and chlorides, carbonates, and nitrates. These may be hydrates. In addition, alkali metal molybdates such as disodium molybdate, alkali metal tungstates such as sodium tungstate, gold cyanides such as potassium gold cyanide, and gold sulfites such as sodium gold sulfite can also be used. The metal salt (a) may be used alone or in combination of two or more kinds.

[0025] Among the above-mentioned metal salts (a), when a nickel salt is contained, it is suitable for depositing a nickel thin film or a nickel alloy thin film by combining an amine borane (b1) and a reducing agent (b2).

[0026] The content of the metal salt (a) in the electroless deposition bath is not particularly limited, but is preferably 0.01 to 0.1 M, more preferably about 0.05 M, from the standpoint of deposition rate of the metal or alloy thin film, uniform deposition, bath stability, and the like.

[0027] As the amine constituting the amine borane (b1), for example, dimethylamine, trimethylamine, etc. are preferable. Among these, dimethylamine is more preferable. Specific examples of the amine borane include dimethylamine borane, trimethylamine borane, etc. Among these, dimethylamine borane is preferable. The amine borane (b1) may be used alone or in combination of two or more kinds.

[0028] The content of amine borane (b1) in the electroless deposition bath is not particularly limited, but is preferably 0.01 to 0.1 M, more preferably about 0.02 M, from the standpoint of deposition rate of the metal or alloy thin film, uniform deposition, bath stability, and the like.

[0029] The reducing agent (b2) is not particularly limited, and examples thereof include phosphorus-containing compounds, amine compounds, boron-containing compounds, aldehyde compounds, formic acid or a salt thereof, etc. The reducing agent (b2) may be used alone or in combination of two or more kinds.

[0030] Examples of the phosphorus-containing compound reducing agent include hypophosphites (e.g., sodium salts, potassium salts, etc.), hydrates thereof, etc. Among these, the phosphorus-containing compounds are suitable for depositing thin films of metals or alloys such as nickel, cobalt, palladium, gold, platinum, etc.

[0031] The amine compound reducing agent may be, for example, hydrazine, etc. The amine compound is suitable for depositing a thin film of a metal or alloy such as cobalt, nickel, platinum, palladium, copper, gold, or silver.

[0032] The boron-containing compound reducing agent may, for example, be a borohydride salt (e.g., a sodium salt, a potassium salt, etc.), etc. The boron-containing compound is suitable for depositing a thin film of a metal or alloy such as nickel, cobalt, palladium, platinum, copper, silver, or gold.

[0033] The aldehyde compound reducing agent may be, for example, formaldehyde, etc. The aldehyde compound is suitable for depositing a thin film of a metal or alloy such as copper, gold, silver, platinum, or palladium.

[0034] Among the above-mentioned reducing agents (b2), those containing a phosphorus-containing compound are suitable for depositing a thin film of a phosphorus alloy such as nickel.

[0035] The content of the reducing agent (b2) in the electroless deposition bath is not particularly limited, but is preferably 0.1 to 0.2 M, more preferably about 0.18 M, from the standpoint of deposition rate of the metal or alloy thin film, uniform deposition, bath stability, and the like.

[0036] Other components may be added to the electroless deposition bath in addition to the metal salt (a), the amine borane (b1), and the reducing agent (b2). The other components are not particularly limited, but include, for example, known components added to electroless deposition baths, and specific examples thereof include, for example, complexing agents such as organic acids, amino acids, and amines, stabilizers such as lead salts, bismuth salts, and sulfur compounds, pH adjusters such as hydrochloric acid, sulfuric acid, phosphoric acid, sodium hydroxide, potassium hydroxide, and ammonia water, pH buffers such as phosphates, carbonates, organic acids, and boron compounds, and nonionic, anionic, cationic, and amphoteric surfactants.

[0037] The pH of the electroless deposition bath is preferably alkaline, more preferably about 10. The temperature of the electroless deposition bath when the anion exchange membrane to which silver catalytic nuclei have been applied is immersed in the electroless deposition bath for electroless deposition is preferably higher than room temperature, more preferably about 60°C in consideration of a moderate deposition rate and bath stability. The electroless deposition time is selected according to the desired film thickness of the metal or alloy thin film. The anion exchange membrane to which silver catalytic nuclei have been applied may be subjected to a pretreatment such as washing with water to clean the surface before immersion.

[0038] The metal or alloy thin film deposited on the anion exchange membrane by electroless deposition is not particularly limited, but may be a metal or alloy thin film containing a transition metal element. Examples of the transition metal element include nickel, iron, cobalt, copper, platinum, palladium, gold, molybdenum, tungsten, and rhenium. Boron B and phosphorus P may be included in the thin film deposited by electroless deposition, and may be co-deposited with the metal as an alloy containing these elements. A bath containing a combination of amine borane (b1) and reducing agent (b2) is suitable for depositing a nickel thin film or an alloy thin film mainly composed of nickel.

[0039] The thickness of the metal or alloy thin film is not particularly limited and is adjusted depending on the application.

[0040] The method of the present invention can be suitably used in processes for forming a cathode / anode catalyst layer for improving the performance and efficiency of an anion exchange membrane water electrolysis device, and can be applied as a catalyst for the hydrogen evolution reaction (HER). The anion exchange membrane provided with a metal or alloy thin film produced by the method of the present invention may be further coated with a thin film by applying an electrodeposition process, if necessary, for the purpose of improving the functionality of the catalyst layer. EXAMPLES

[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. <Example 1> 1. Addition of Ag catalyst core An anion exchange membrane (A201, Tokuyama Corp.) was immersed in a dilute sulfuric acid aqueous solution at room temperature for 30 seconds for acid cleaning. After rinsing with ultrapure water, it was immersed in an aqueous solution containing AgNO3 (0.01M) and HCl (35% solution at 2.5mL / L) at room temperature for 60 seconds to be modified with Ag catalyst core precursor. The anion-exchange membrane modified with the Ag catalyst core precursor was washed with water and then immersed in an aqueous solution containing dimethylamine borane (DMAB, 0.05M) at room temperature for 60 seconds to reduce the Ag catalyst core precursor and precipitate the Ag catalyst core.

[0042] 2. Electroless deposition An aqueous solution containing NiSO4 (0.05M), FeSO4 (0.05M), dimethylamine borane (DMAB, 0.02M), sodium hypophosphite (0.18M), ammonium sulfate (0.4M), and citric acid (0.2M) at pH 10 was prepared as an electroless deposition bath. The anion exchange membrane with Ag catalytic cores was washed with ultrapure water and then immersed in an electroless deposition bath at 60°C for 15 minutes. A thin NiFeP film was deposited on the surface of the anion exchange membrane with Ag catalytic cores, covering the entire surface (Fig. 1(A)). The thickness of the NiFeP thin film was several μm. When a deposition bath was used that did not use DMAB as the reducing agent but used only hypophosphorous acid as the reducing agent, electroless deposition did not occur and no NiFeP thin film was deposited (Fig. 1(B)).

[0043] The results of EDX analysis of the deposited alloy film composition are shown in Table 1. The left side shows the result when Ag was used as the catalyst nucleus, and the right side shows the result when Pd (Non-Patent Document 1) was used as the catalyst nucleus instead of Ag. It was revealed that the same alloy film composition as when Pd was used as the catalyst nucleus was obtained when Ag catalyst nucleus was used.

[0044] [Table 1]

[0045] Electrochemical measurements were carried out to evaluate the HER performance of the NiFeP layer formed on the anion exchange membrane. The NiFeP layer formed on the anion exchange membrane was used as the cathode, and Ni foam was used as the anode. The electrode areas of the cathode and anode were both 10 × 10 mm 2 The electrochemical measurements were carried out using a standard cell equivalent to the membrane electrode assembly structure (Int. J. Hydrogen Energy, 46, 36619-36628 (2021)). The electrolyte was a 1 M K2CO3 solution, and the current was measured at -500 mA cm using a potentiostat / galvanostat device manufactured by Hokuto Denko Corporation. -2 Constant-current electrolysis was performed for 30 min at 1000 K. Figure 2 shows the potential profile of constant-current electrolysis of the electrode. It was demonstrated that the NiFeP electrode prepared by electroless deposition functions as a catalytic electrode for HER.

[0046] <Example 2> 1. Addition of Ag catalyst core An anion exchange membrane (A201, Tokuyama Corp.) was immersed in a dilute sulfuric acid aqueous solution at room temperature for 30 seconds for acid cleaning. After rinsing with ultrapure water, it was immersed in an aqueous solution containing AgNO3 (0.01M) and HCl (35% solution at 2.5mL / L) at room temperature for 60 seconds to be modified with Ag catalyst core precursor. The anion-exchange membrane modified with the Ag catalyst core precursor was washed with water and then immersed in an aqueous solution containing dimethylamine borane (DMAB, 0.05M) at room temperature for 60 seconds to reduce the Ag catalyst core precursor and precipitate the Ag catalyst core.

[0047] 2. Electroless deposition An aqueous solution containing COSO4 (0.05 M), dimethylamine borane (DMAB, 0.02 M), sodium hypophosphite (0.18 M), ammonium sulfate (0.4 M), and citric acid (0.2 M) at pH 10 was prepared as an electroless deposition bath. The anion exchange membrane with Ag catalytic cores was washed with ultrapure water and then immersed in an electroless deposition bath at 60°C for 30 minutes. It was confirmed that a thin film of Co was deposited on the surface of the anion exchange membrane with Ag catalytic cores, covering the entire surface.

Claims

1. A method for producing a metal or alloy thin film-applied anion exchange membrane, comprising the steps of: providing silver catalyst nuclei on at least one surface of the anion exchange membrane; and A method for producing an anion exchange membrane provided with a metal or alloy thin film, comprising the steps of: immersing an anion exchange membrane provided with silver catalytic nuclei in an electroless deposition bath containing (a) one or more metal salts, (b1) an amine borane, and (b2) a reducing agent appropriate for the metal or alloy to be deposited, thereby reducing the metal salt and depositing the metal or alloy on the surface of the anion exchange membrane provided with the silver catalytic nuclei.

2. The method for producing an anion exchange membrane provided with a metal or alloy thin film according to claim 1, wherein the reducing agent (b2) comprises a phosphorus-containing compound.

3. The method for producing an anion exchange membrane provided with a metal or alloy thin film according to claim 1 or 2, wherein the metal salt (a) comprises a nickel salt.